An accurate fault location method for distribution network based on active transfer arc-suppression device. (November 2021) - Qiao, Jian; Yin, Xianggen; Wang, Yikai; Xu, Wen; Tan, Liming
Abstract: Active transfer arc-suppression device is a kind of arc suppression device which has been widely used in the distribution network. When a single-phase grounding fault occurs, the bus of faulty phase is actively grounded metallicity in the substation to limit the voltage of faulty phase, so as to realize arc extinction. In this paper, an accurate fault location method is proposed for the distribution network equipped with active transfer arc-suppression device. According to the variation characteristics of the fault traveling wave signals before and after arc-suppression device operation, the fault location formula based on the traveling wave velocity difference of different modes and the fault location formula based on the mutation of aerial-mode traveling wave are combined to obtain the final fault location method that is not affected by ground-mode wave velocity. The proposed method expands the function of active transfer arc-suppression device, makes it have additional fault location ability, and greatly improves the economy of the device. Simulation verifies that the proposed method is not affected by fault conditions, soil resistivity and extreme fault. The absolute error is within 50 m in all cases, which has high reliability.